Factors Related to Employer Health Insurance Contribution During COVID-19 Epidemic in Indonesia - Rusmitasari, Heni; Supriatin, Supriatin; Sadli, Mohamad; Amaliah, Lili; Tresnawan, Teten; Suyitno, Suyitno; Maretalinia, Maretalinia (JURNAL INFO KESEHATAN, 2023)
The COVID-19 pandemic impacted all sectors of the world, including business. In fact, the employer faced a collapse, and many employees were determined. Another issue is health insurance, which might change before and during the pandemic. The objective of this study was to examine the factors associated with the employer’s contribution to health insurance during COVID-19. The secondary data, “Rapid Gender Assessment Survey 2021”, was used on 239 employees in Indonesia. The dependent variable in this study was employer contribution to health insurance during the pandemic (yes or no) and the main independent variable was employer contribution before the pandemic. Other sociodemographic variables were also included in the model as controls. This study used univariate, bivariate, and multivariate (binary logistic regression). The result of this study revealed that employers who contributed to health insurance before the pandemic tend to contribute again to health insurance during the pandemic. This study also reviews the legal law, including regulations about national health insurance and employment. The government’s intention is needed to ensure the rights of employees are well realized.